Adsorção de cromo hexavalente por carvão ativado granulado comercial na presença de surfactante aniônico (LAS) - SILVA, Maria Vitória Roma da (Universidade Federal do Pará, 2013)
The hexavalent chromium removal from solutions of anionic surfactant (LAS) by granular activated carbon (GAC) commercial was studied. At CAG characterization was used ASTM standard method (Sauter mean diameter, dDMS e pH) and method BET (S, specific surface area). Adsorbent surface group and PCZ were determined by the method of Boehm and potentiometric titration, respectively. The adsorbent characterization results: dDMS=2.4 mm, pH=9.0,S=677.4 m²/g; basic groups (70%) compared with the acidic groups and PCZ in the range (4.8 – 8.6). Tests of adsorption of the surfactant LAS were carried out in shaker (140 rpm/24 h./27ºC), 2.0 g CAG/50 mL, the LAS concentration were determined by methylene blue standard method. The removal results versus initial concentration and removal versus time of all LAS concentrations were more than 99%. The adsorption of Cr(VI) (5 – 20 mg/L) were carried out in thermostatic bath (140 rpm/27ºC); 2,0 g CAG/50 mL; 1 and 24 hours of processing; without and with addition of surfactant (70, 140, 210, 280, 350, 533 and 700 mg/L). The initial e residual concentrations of metal were determined by 1,5-diphenylcarbazide colorimetric method. The metal removal without the addition of LAS was not satisfactory values were obtained, around 15%. The metal removal with surfactant reached values, around 70% to the lowest metal concentration (5 mg/L) and between (58-65%) for the other concentrations.